EFEKTIVITAS RADIO SPOT TERHADAP PENINGKATAN PENGETAHUAN TENTANG PERAWATAN KESEHATAN ORGAN REPRODUKSI PADA SISWA SMP 2 SUBAH KABUPATEN BATANG JAWA TENGAH TAHUN 2016 - Rizka Fauza; Kismi Mubarokah (Dian Nuswantoro Semarang, 2020)
Background: Adolescent reproductive health problems partly because of the lack of information on reproductive health care. Information about reproductive health care should be given to adolescents through various media such radio spot.Objective: The aims to analyze the effectiveness of radio spots media for 2nd grade students of Senior High School, Subah.Methods: This study used a combination study with sequential exploratory design. Then used approach on quantitative research phase was the pre-experimental design one group pretest-posttest design. The first step of the research was an interview for requirements analysis; second, wrote radio script spot; third, a feasibility test spot radio script; fourth, radio spots production; fifth, cognitive pretest; Sixth, radio spot exposure to students; and last cognitive post-test. The sample size was 276 respondents then bivariate analyzed by used Wilcoxon test.Result: The results of this study was an average of study subjects stated reproductive health care can be done only by cleaning the reproductive organs after urination. More of respondents used local language to speak reproductive health term. There were differences in knowledge prior to exposure to radio spots on reproductive health care knowledge after exposure to radio spots on reproductive health care (p = 0.0001). Increase of knowledge was 29.17% as a result of exposure to radio spots.Conclusions: Schools are advised to sustain playing the radio spot about reproductive health care periodically and continuously as well as the need for the development of reproductive health materials according to the development situation of students.Keywords: Radio Spot, Media, Reproductive, Subah.